MAMBALEH NAN TALIPEK TERINSPIRASI DARI KEGIATAN MANGANYAM KAMPIA DI MATUA KABUPATEN AGAM - Putri, Wulan Indah; Emri, Emri; Stevenson, Yan (Institut Seni Indonesia Padangpanjang, 2023)
The Mambaleh Nan Talipek dance work departs from manganyam kampia activities in Matur, Agam Regency. The creators chose to transform the woven techniques such as the lipek technique and the twisting technique onto the dancer's body, so that in making the work they are more focused on developing the woven technique into the structure of the dance work by Mambaleh Nan Talipek which is divided into three parts. In the first part, the artist transforms the lipek technique using his hands, feet and body. The second part transforms the weaving technique by using the properties of the cloth and in this part the dancers perform complementary movements. In the third part, the artist shows the woven Kampia into dance. In this section, Kampia is used to show how the results of the two techniques are formed. This work is strengthened by live music and other compositional elements, the methods used in composing this work are methods of exploration, improvisation, observation, and formation. This work is supported by seven female dancers, with cultural themes and non-dramatic types.